Genetic Studies Relating to the Production of Transformed Clones Diploid in the Tryptophan Region of the Bacillus subtilis Genome - Audit, C. (1973)
Transformation experiments with Bacillus subtilis strains carrying trpE26 (the marker responsible for the detection of merodiploid clones after transformation or transduction) have established the precise position of this marker on the “aromatic region” of the chromosome, at the distal end of the anthranilate synthetase locus. Integration efficiency of the mutant allele (trpE26) seems to be very low. Co-transfer of markers situated on either side of it is almost nil when both donor and recipient carry this mutation. The “exclusion” of trpE26 does not, however, affect recombination frequencies for nearby markers. To explain these facts we considered the hypothesis of a preferential breakage of the deoxyribonucleic acid (DNA) at the trpE26 site or that of an insertion mutation. These studies have also demonstrated the establishment of physical linkage of a marker from the exogenote (hisH2) to a resident marker (tyrA1) in stable and unstable merodiploid clones, thus confirming integration of the donor DNA segment into a genetic structure of the recipient. Furthermore, duplication was shown in merodiploid clones (through reversion and transformation) for a locus of the recipient (tyrA) which was not involved in the initial transformation. This suggests that the diploid condition in this region extends beyond the transformed area. Interpretation of the genetic constitution of these partial diploids calls for postulation of the existence of long duplications, a second (incomplete) chromosome, or an episome-like element.